Canada's Visa Requirement For Mexicans and Its Political Rationalities - Liette Gilbert (Norteamérica)
In July 2009, the Harper government imposed a visa requirement on all Mexicans traveling to Canada. The Canadian government legitimized its decision by alluding to the rising number of requests for refugee status from México. This article examines the official rhetoric used by Conservative politicians to rationalize this requirement and immigration and refugee law reform. I argue that the imposition of the visa intended to stop refugee claimants from México also serves to criminalize them using official rhetoric and prejudicial language. That discourse implies the bilateral denial of the human rights crisis created by narco-violence and corruption.